Design and implementation of nonlinear control laws for a stepper motor - Ngai, Hin Sung. (2008)
In this thesis, the control problem of a permanent magnet (PM) stepper motor system using nonlinear control techniques is investigated. A thorough study of the dynamic model of the permanent magnet stepper motor is carried out and the parameters of the motor are estimated using the least square estimation technique. Several nonlinear control schemes are then investigated. A feedback linearization controller, a Corless/Leitmann type controller, a continuous nonlinear state feedback controller, two linear robust controllers, a static sliding mode controller and a dynamic sliding mode controller are used to regulate the position of the shaft of the motor under different loading conditions. Actual implementation of these control schemes is then carried out using the DS1102 controller board that is based on the Texas Instrument DSP TMS320C30 floating-point processor. To test the performance of the system under different loading conditions, various loads are attached to the shaft of the motor.